Impact of pharmacist led mobile application on medication adherence and efficacy in chronic kidney disease - Shaza Gamal; Ahmad Mohamad Abbas Elseasi; Nirmeen Ahmed Sabry; Samar Farghali Farid (npj Digital Medicine)
Abstract Medication adherence is crucial for slowing chronic kidney disease (CKD) progression. A specially designed pharmacist-led mobile application, Kidney Health, was evaluated in a single-center, prospective, 3 months, randomized controlled trial (RCT) to assess its impact on medication adherence and efficacy in patients with CKD. 86 patients were randomly assigned to control group, who received standard of care, and app group, who in addition, had access to Kidney Health. The primary outcome was medication adherence measured by simplified medication adherence questionnaire (SMAQ). Other outcomes evaluated included kidney function, blood pressure, and random blood glucose (RBG). The app group showed a significant increase in adherent patients (P < 0.001) and decreased RBG (P = 0.047). Adherent patients increased (P = 0.002) and RBG decreased (P = 0.006) in app group compared to control group at the end of the study. Kidney Health has shown potential for encouraging patients with CKD to adhere to their medication and improving their clinical outcomes. Trial registration: clinicaltrials.gov with ID: NCT05168449, Date of registration: 12/2021 https://clinicaltrials.gov/study/NCT05168449 .